THE INFLUENCE OF TAX EXAMINER COMPETENCE AND ETHICS AGAINST THE COMPLAINCE OF TAX EXAMINATION PROCEDURES AND THE IMPLICATION ON ACCEPTABILITY OF TAX AUDIT REPORT (An Empirical Study on Regional Office Directorate General in East Java After of The - Heru Tjaraka (Indonesian Journal of Economics and Business, 2011)
This dissertation analyzing the competence and ethics of tax examiner on his compliance with tax audit procedures and their implication on the acceptability of the audit report. As such, it takes an empirical research at take place the Regional Tax Office of East Java Post Organizational Reform.As this study employs a qualitative approach, analyses and measurements are focused on the values of the answers according to the Likert scale with regard to questionaires made by respondents. By employing the random sample formula, some of 197 respondents are selected from employees of that Regional Office.  This research demonstrates that there is a significant influence whether partially or simultaneously made by the competence of examiner and ethics on the compliance with audit procedures in that Region. In addition, the competence of examiner, ethics and his compliance with the audit procedures also partially and simultaneously influence significantly on the acceptability of the audit report.